Determinants of psychological and social adjustment among cardiac rehabilitation patients: Personal resources, stress, and coping strategies. - Cazabon, Andrée M. (University of Ottawa (Canada), 1991)
The primary objectives of this study were: to determine the predictors of psychological distress and social maladjustment (i.e., social interaction, work, and home management functioning), to determine the relationship between specific coping strategies and psychological distress and social maladjustment, and to determine the effects of program participation on patients' level of personal mastery, cardiac functional capacity, frequency of stressors, and coping strategies. The sample comprised 223 males between the ages of 27 and 66 who had heterogeneous CHD diagnoses. The data were collected by means of standardized questionnaires using a mailing procedure which achieved a response rate of approximately 90% across time points. The results of multiple hierarchical regression analyses revealed that number of hassles and disengagement coping contributed significant increments to the variance explained in psychological distress. Higher levels of engagement and symptom management coping, however, were not found to be significant predictors of lower psychological distress in this study. For social maladjustment, in general, neither stress nor coping emerged as consistent predictors of social maladjustment across time points. Coping consistently emerged as a stronger predictor of both psychological distress and social maladjustment when current coping strategies were used as predictors (Model B), as opposed to when coping strategies from the previous time point were entered (Model A). Regarding the relationships among specific coping strategies and psychological distress and social maladjustment, the disengagement coping strategies had stronger positive correlations with psychological distress and one of the three social maladjustment outcomes than did engagement coping, which had fewer and weaker positive correlations with these outcomes. Program participation did not predict personal mastery or use of coping strategies, but did predict fewer hassles. The number of physiotherapy sessions received predicted level of cardiac functional capacity. Furthermore, greater cardiac functional capacity was predicted by higher personal mastery, fewer hassles, lower psychological distress, and less impairment in domestic activity. This study demonstrates the importance of psychosocial variables as predictors of cardiac functional capacity, and provides empirical evidence that these variables moderate the relationship between physical status and recovery level. The findings concerning the identification of predictors of adjustment provide information for developing rehabilitation interventions for CHD patients. Patients' adjustment may be facilitated by reduction of hassles, limiting use of disengagement coping strategies, and strengthening personal mastery. The methodological strengths and weaknesses of this study are discussed, as are its implications for coping theory and research. (Abstract shortened by UMI.)
Keywords: Psychology, Clinical.